HUBUNGAN MOTIVASI KERJA DENGAN KEDISIPLINAN GURU TK DI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Fitri Rahmawati; Daviq Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : Based on the fact that the reseacher observed in the field, that was still less of working motivation of kindergarten teacher and lack of discipline in carrying out their duties. It can be seen there were teachers still who are not disciplined in teaching, there were teachers still who often procrastinate her work, teachers leave early, teachers who still work with did not use time very well, if there was no class for teaching the teacher did not come to school. This occurred because of the assumption of the teachers that working as government officials did not have to work optimally because of salary amount has been determined in accordance with applicable government regulations. The existence of this view made there was no initiative or motivation of teachers in working. These conditions will affect the performance of teachers, because teachers lack the motivation to follow rules of school. The purpose of this study was to determine the relationship working motivation Discipline of Kindergarten Teacher in Bukit Batu District, Bengkalis Regency. The population in this study was the entire kindergarten teachers in Bukit Batu district, Bengkalis Regency. There were 51 teachers from 10 kindergartens. The number of samples in this study was 51 teachers. While, in try out the researcher used 20 teachers from Bukit Raya Pekanbaru district. From the results of this research, it can be seen from Kolmogorov-Smirnov column that significant value in working motivation was (0,200) and discipline of teachers was (0,200), based on the results of the homogeneity test analysis, statistical values obtained at 0.698 and the probability value of 0,135, and the resulting coefficient of determination was r 2 = 0,451 and p = 0,000 (p <0,05), it can be seen that the effect of working motivation was 45,1% to discipline of teachers. From the analysis of simple correlation (r) obtained a correlation between working motivation with the level of teachers discipline (r) was 0,672 with a probability value was 0,000. Therefore the probability <0,05 (0,000 <0,05), then Ho was rejected. This suggests that there was a strong relationship between working motivation with discipline of teachers. The level of the relationship between the two variables were in a strong category was 67,2%.Key word: Working with the Disciplinary Teacher Motivation